Crown of midnight : a Throne of Glass novel - Maas, Sarah J. (New York : Bloomsbury, 2014)
Includes excerpt from Heir of Fire, the next book in the series.
As the royal assassin to an evil king, eighteen-year-old Celaena Sardothien must decide what she will fight for-- survival, love, or the future of a kingdom.
Sequel to: Throne of glass.
Keywords: Assassins -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Love stories; Assassins -- Fiction; Kings, queens, rulers, etc. -- Fiction; Courts and courtiers -- Fiction; Love -- Fiction; Young adult fiction; Fantasy fiction